CO2 diffusive characteristics and influencing factors in the porous medium with saturated polyacrylamide solutions - Qingchao Cheng; Guangsheng Cao; Peilun Wang; Ruixuan Bu; Yujie Bai (Arabian Journal of Chemistry, 2023)
Polyacrylamide has been widely utilized to store CO2 in reservoirs in order to alleviate the greenhouse impact. However, no studies have been conducted on the motion of CO2 in a polyacrylamide solution within porous media. This study illustrates the effect of polyacrylamide molecular weight, concentration, pressure, temperature, and pore size on the dynamic diffusion of CO2 in the core with saturated polyacrylamide solutions. The diffusion motion characteristics of CO2 were obtained by diffusion experiments. The microscopic analysis of core slices following testing showed the presence of polyacrylamide on rock particles. The pressure and CO2 mass fraction distribution inside the core were calculated by constructing a mathematical model. The results show that the increase in molecular weight and concentration of polyacrylamide decreased the diffusion ability of CO2, while temperature and pressure accelerated the diffusion of CO2. The polyacrylamide moved into the core to form an effective inhibiting effect, which was affected by CO2 and pressure. While the increase in pore size accelerates the flow rate of the polyacrylamide, it also enhances the sealing capacity of the polyacrylamide solution. Scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) showed that the core had a high content of polyacrylamide solution inside it, and these molecules were attached to the surface of the core particles in an irregular lamellar pattern. The calculation model was consistent with the diffusion experimental results, where the CO2 diffusion coefficient in the polyacrylamide solution was in the order of 10-12 m2/s under the conditions of 5–30 MPa, 323–343 K, and a core permeability of 60 × 10-3 μm2. The results of this paper provide a new calculation for evaluating the performance of polymer plugging.